Differential inactivation of polymorphic variants of human O(6)-alkylguanine-DNA alkyltransferase - Fang, Qingming (2007)
The human DNA repair protein O(6)-alkylguanine-DNA alkyltransferase (hAGT) is an important source of resistance to some therapeutic alkylating agents and attempts to circumvent this resistance by the use of hAGT inhibitors have reached clinical trials. Several human polymorphisms in the MGMT gene that encodes hAGT have been described including L84F and the linked double alteration I143V/K178R. We have investigated the inactivation of these variants and the much rarer variant W65C by O(6)-benzylguanine, which is currently in clinical trials, and a number of other second generation hAGT inhibitors that contain folate derivatives (O(4)-benzylfolic acid, the 3' and 5' folate esters of O(6)-benzyl-2'-deoxyguanosine and the folic acid γ ester of O(6)-(p-hydroxymethyl)benzylguanine). The I143V/K178R variant was resistant to all of these compounds. The resistance was due solely to the I143V change. These results suggest that the frequency of the I143V/K178R variant among patients in the clinical trials with hAGT inhibitors and the correlation with response should be considered.